Penentuan Kesetimbangan Adsorpsi Regenerated Spent Bleaching Earth (RSBE) Terhadap Ion Cu(II) - S, Andi Muhammad; Yusnimar, Yusnimar; Helianty, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Spent bleaching earth (SBE) is the waste that generated from bleaching units in palm oil refining industry. Solution for the waste reduction is regenerating SBE into regenerated spent bleaching earth (RSBE) which can be used as adsorbent heavy metals in waste waters such as Cu(II) derived from the industry. In this study SBE regenerated by extracting oil soxhletation at 72oC for 8 hours with solvent n-hexane, then washed with 3% HCl and finally physically activated at a temperature of 470oC. This study aims to determine the adsorption capability of RSBE and the corresponding adsorption isotherm models. A total of 1 g RSBE mixed with a solution of CuSO4 with a volume of 100 ml at various concentrations (10, 15, 20, 25 and 30 ppm). The results showed that the ion adsorption of Cu(II) by RSBE reached equilibrium after 30 minutes of contact time, and adsorption occured by following the Langmuir isotherm adsorption models with correlation coefficient (R2) was 0.956 and the maximum value of adsorption capacity is 7.41 mg Cu(II)/g RSBE.Keywords: adsorption, adsorption isotherms, ion Cu (II), SBE, RSBE.